Analysis And Implementation Of Triple-Tuning Filters For Harmonic Reduction In Electrical Power Systems - Marwan Affandi; Bagus Saputra; Muhammad Roihan Fuady; Raffi Hidayat; Anggi Nur Ananda Saragih; Rut Omega (Jurnal Teknik Elektro dan Komputer TRIAC, 2025)
This research aims to develop an effective solution to reduce harmonics through the design and implementation of a triple-tuning filter. High harmonic levels, which exceed the IEEE 519-2014 standard limits, can reduce system efficiency and power quality. The research method includes a literature study and simulation using MATLAB software. This simulation designs a triple-tuning filter with three LC resonance branches to suppress fifth, seventh, and eleventh order harmonics. The prototype design was tested based on electrical load condition data at the Electrical Engineering Department Building of Medan State University. The simulation results show that the triple-tuning filter significantly reduces the Total Harmonic Distortion (THD) value. The initial THD value of 31.8 percent was successfully reduced to below the standard limit of five percent. In conclusion, the triple-tuning filter has been proven to be an effective and applicable solution in harmonic mitigation in power systems, while also providing practical and academic contributions in the field of Electrical Engineering.